New electrolyte mixture of propylene carbonate and butyltrimethylammonium bis(trifluoromethylsulfonyl)imide (N1114 TFSI) for high performance silicon nanowire (SiNW)-based supercapacitor applications. (10th November 2017) - Lé, Tao; Gentile, Pascal; Bidan, Gérard; Aradilla, David
Abstract: The use of a mixture of propylene carbonate (PC) and N1114 TFSI ionic liquid (50:50% w.t) has been investigated as an optimal electrolyte for symmetric micro-supercapacitors based on SiNWs using a large and stable cell voltage of 3.5 V. The device showed an areal capacitance of 150 μF cm −2, an energy density of 1 mJ cm −2 and a power density of 16 mW cm −2 maintaining an outstanding cycling stability after 3·10 6 galvanostatic charge-discharge cycles at room temperature. Such properties were comparable to those obtained using the pure ionic liquid. Additionally, the excellent electrochemical performances reported in this study reflect the potential of such mixture to be employed as a promising electrolyte in wide operating temperatures ranging from 0 to 80 °C at large electrochemical windows.